2018
DOI: 10.3847/1538-4357/aaab59
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cometary Dust Particles to the Orbit of the Earth: Particle Size, Shape, and Mutual Collisions

Abstract: In this study, we numerically investigated the orbital evolution of cometary dust particles, with special consideration of the initial size frequency distribution (SFD) and different evolutionary tracks according to initial orbit and particle shape. We found that close encounters with planets (mostly Jupiter) are the dominating factor determining the orbital evolution of dust particles. Therefore, the lifetimes of cometary dust particles (∼250 thousand years) are shorter than the Poynting-Robertson lifetime, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
3
3
0
Order By: Relevance
“…Nesvorný, Janches, et al () showed that for various SFDs it is possible to model both the meteor distributions at Earth, meteoroid flux at low Earth orbit, and the latitudinal profile of the Zodiacal cloud. Our selection of SFD is further supported by the recent study of Yang et al (), who suggest similar values of α for the range of diameters of meteoroids considered in the model presented here. We also simplified our selection of SFD such that we use the same SFD for all populations in this manuscript.…”
Section: Model Limitationssupporting
confidence: 87%
“…Nesvorný, Janches, et al () showed that for various SFDs it is possible to model both the meteor distributions at Earth, meteoroid flux at low Earth orbit, and the latitudinal profile of the Zodiacal cloud. Our selection of SFD is further supported by the recent study of Yang et al (), who suggest similar values of α for the range of diameters of meteoroids considered in the model presented here. We also simplified our selection of SFD such that we use the same SFD for all populations in this manuscript.…”
Section: Model Limitationssupporting
confidence: 87%
“…Numerical simulations of the IRAS observations in the thermal domain of the zodiacal cloud based on the dynamical properties of the dust ejected from comets and from asteroids indicates that 85-95% of the mid-infrared emission visible from 1 au is produced by JFCs, while asteroidal and long-period comets are both respectively smaller than 10% (Nesvorný et al, 2010(Nesvorný et al, , 2011. Similar conclusions are reached with the dynamical study of the evolution of aggregate dust particles injected in the inner solar system by active comets and with a size frequency distribution like the one of 67P/Churyumov-Gerasimenko, as they can reproduce the interplanetary dust properties detected around the Earth's orbit (Yang & Ishiguro, 2018). Consistent results were also obtained from the study of the Doppler shift from the Fraunhofer lines of the scattered solar light (Ipatov et al, 2008).…”
Section: Phase Angle Variationssupporting
confidence: 73%
“…In order to obtain specific properties of the dust particles, it is mandatory to invert the integrated intensity and polarization. Knowing that the zodiacal cloud is seen to be relatively homogeneous and in an apparent steady state, which is consistent with the mixing of injected dust particles and their short lifetimes (Campbell-Brown, 2008;Nesvorný et al, 2011;Yang & Ishiguro, 2018), it is possible to invert the light integrated over the line-of-sight to deduce local scattering properties of the dust particles. Local rigorous inversion and local inversions through mathematical methods are, together with their main results, summarized in Levasseur-Regourd et al (2001), section 4.…”
Section: Inversion Methodsmentioning
confidence: 75%
“…The collisional lifetime of mm-scale particles at 1 AU is estimated to be τ col 10 5 yr, modeled with the orbital distribution of sporadic meteors measured by radar (Nesvorný et al, 2011) (cf. τ col ∼ 10 4 or 10 5 yr, Grun et al, 1985;Soja et al, 2016;Yang and Ishiguro, 2018). On the other hand, Poynting-Robertson (P-R) and solar-wind drag cause dust particles to spiral down to the Sun.…”
Section: Zodiacal Cloudmentioning
confidence: 99%